THE INCREASE OF SERVICE DURABILITY OF THE TECHNOLOGICAL TOOL OF PIERCING MILL OF THE TUBE-ROLLING SHOP - A. V. Vengura; S. V. Avdeev; S. V. Agafonov; V. N. Kovaliov (Литьë и металлургия)
The increase of service durability of the technological tool of piercing mill of the tube-rolling shop due to optimization of the geometrical sizes of the applied tool is considered. After changing of the geometrical sizes of the piercing mill technological tool, it was set as a purpose to redistribute the elementary efforts of deformation perceived by piercing mandrel and rollers of piercing mill along the length of their working surfaces. It was succeeded to increase service durability of the piercing mandrels not less than by 30% as a result of the carried-out work.